2020
DOI: 10.1136/bmjdrc-2019-000892
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Mobile-based Artificial Intelligence Algorithm in the detection of Diabetic Retinopathy (SMART) study

Abstract: IntroductionThe aim of this study is to evaluate the performance of the offline smart phone-based Medios artificial intelligence (AI) algorithm in the diagnosis of diabetic retinopathy (DR) using non-mydriatic (NM) retinal images.MethodsThis cross-sectional study prospectively enrolled 922 individuals with diabetes mellitus. NM retinal images (disc and macula centered) from each eye were captured using the Remidio NM fundus-on-phone (FOP) camera. The images were run offline and the diagnosis of the AI was reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 18 publications
5
38
1
2
Order By: Relevance
“…At individual level, we report high sensitivity for ARIA in detecting any DR (91.4%). This is similar to that reported by Rajalakshmi et al (2018) where they used an alternate AI system, (EyeArt), at a tertiary care diabetes centre in India, capturing three retinal images using a smartphone‐based device and reported a sensitivity of 95.8% for detection of any DR. Another study, using the Medios AI system, captured two retinal images and reported similar sensitivity and specificity values 26 . The high sensitivity produced for any DR in this study suggests that the ARIA used is a useful primary‐care tool for triaging to human graders and ultimately reducing the workload, time, cost and variability of human DR grading.…”
Section: Discussionsupporting
confidence: 54%
“…At individual level, we report high sensitivity for ARIA in detecting any DR (91.4%). This is similar to that reported by Rajalakshmi et al (2018) where they used an alternate AI system, (EyeArt), at a tertiary care diabetes centre in India, capturing three retinal images using a smartphone‐based device and reported a sensitivity of 95.8% for detection of any DR. Another study, using the Medios AI system, captured two retinal images and reported similar sensitivity and specificity values 26 . The high sensitivity produced for any DR in this study suggests that the ARIA used is a useful primary‐care tool for triaging to human graders and ultimately reducing the workload, time, cost and variability of human DR grading.…”
Section: Discussionsupporting
confidence: 54%
“…10 Finally, artificial intelligence coupled with telemedicine and mHealth could help to reach populations with poor health system access, either because of geographical isolation or scarcity of human resources for eye health. 280,284 There is little information on implementing artificial intelligence in eye health delivery and even less on whether it could improve care or outcomes. Before deployment into routine clinical practice, artificial intelligence applications require external validation on data that were not previously used in algorithm development and should undergo rigorous safety and efficacy testing in prospective clinical studies.…”
Section: Artificial Intelligencementioning
confidence: 99%
“… 10 Finally, artificial intelligence coupled with telemedicine and mHealth could help to reach populations with poor health system access, either because of geographical isolation or scarcity of human resources for eye health. 280 , 284 …”
Section: Section 6: Beyond 2020—delivering High-quality Universal Eyementioning
confidence: 99%
“…Bias could have been introduced by poor reporting of patient characteristics of the included studies. Finally, except for Abramoff et al’s trial [ 15 ] and 5 other prospectively conducted studies [ 48 , 52 , 55 , 60 , 66 ], all other studies on ML-based DR diagnosis were validated by retrospective data. Due to spectrum bias, an overestimation of ML’s performance in a real-world setting is possible and should be considered.…”
Section: Discussionmentioning
confidence: 99%